2
$\begingroup$

Given $f:\Bbb C^{n}\to\Bbb C$ identified with $f:\Bbb R^{2n}\to\Bbb C$, in a book I read that $$ \partial_x f\,dx+\partial_yf\,dy=\partial_zf\,dz+\partial_{\bar z}f\,d\bar z $$ and that this could be rewritten as $$ df=\partial f+\bar{\partial}f $$ and this last equation defines $\partial f$ and $\bar{\partial}f$.

My problem is to write explicitly the last two objects.

Now $\partial_x:=(\partial_{x_1},\dots,\partial_{x_n})$ and $dx:=(dx_1,\dots,dx_n)$ and so on for the other variables.

Hence we can think at $\partial_x f\,dx$ as a scalar product between $\partial_x f$ and the formal vector $dx$. In this way, writing formally $dz=dx+idy$ and $d\bar z=dx-idy$ we deduce easily the first equation. However I would like to write explicitly both its sides.

LHS it's obviously $df$ (just a computation). Now it would be nice to write explicitly even RHS, in order to understand how to define properly $\partial f$ and $\bar{\partial}f$.

We know that $\partial_z=\frac12(\partial_x-i\partial_y)$ and $\partial_\bar z=\frac12(\partial_x+i\partial_y)$. My problem is to understand how $dz$ works.

We can assume wlog $n=1$. As a differential form, $dx$ is a covector: $dx=(1,0)$ and similarly for $dy=(0,1)$. What about $dz$? We know it's equal to $dx+idy=(1,0)+i(0,1)$, but the "ambient" in which $dz$ lives is 1-dim covector.

I think the point is inside the last observation.

The only way to obtain the first equality directly is to write $dz=(1,-1)$ and $d\bar z=(1,1)$, i.e. $i(0,1)=(0,-1)$. How can this be possibile?

I need someone shading lights on this!

Thank you all!

$\endgroup$
2
$\begingroup$

I don't see how you arrive at your conclusion. In $x,y$ coordinates,

$$ \begin{align}\frac{\partial f}{\partial x} \, \mathrm{d}x + \frac{\partial f}{\partial y} \, \mathrm{d}y &= \frac{\partial f}{\partial x} (1,0) + \frac{\partial f}{\partial y} (0,1) \\&= \left( \frac{\partial f}{\partial x}, \frac{\partial f}{\partial y} \right) \end{align}$$

$$ \begin{align}\frac{1}{2}\left( \frac{\partial f}{\partial x} - i \frac{\partial f}{\partial y} \right) \, \mathrm{d}z &+ \frac{1}{2}\left( \frac{\partial f}{\partial x} + i \frac{\partial f}{\partial y} \right) \, \mathrm{d}\bar{z} \\&= \frac{1}{2}\left( \frac{\partial f}{\partial x} - i \frac{\partial f}{\partial y} \right) (1,i) + \frac{1}{2}\left( \frac{\partial f}{\partial x} + i \frac{\partial f}{\partial y} \right) (1,-i) \\&= \left( \frac{\partial f}{\partial x}, \frac{\partial f}{\partial y} \right) \end{align}$$

$\endgroup$
1
  • $\begingroup$ I'm drunk but I'm not aware of being it. It's the only explanation :( thanks a lot $\endgroup$ – Joe Jan 9 '15 at 16:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.